Analysis of The Influence of UMKM, Foreign Direct Investment (FDI) and Government Capital Expenditures on Unemployment in Indonesia - Faizal, Moh; Fattah, Sanusi; Hamrullah (PT. Maju Malaqbi Makkarana, 2023)
This study aims: 1) To analyze the influence of MSMEs on unemployment in Indonesia, 2) To analyze the effect of foreign direct investment (FDI) on unemployment in Indonesia, and 3) To analyze the effect of government capital expenditure on unemployment in Indonesia. The data collection in this study was carried out by searching documentation or information publications. Data analysis was performed using the Ordinary Least Square analysis method. The results of the study: 1) SMEs have a negative effect, both directly and indirectly on unemployment. If MSMEs increase, unemployment will decrease, 2) Foreign Direct Investment (FDI) has a negative effect, both directly and indirectly on unemployment. If foreign direct investment increases, unemployment will decrease, and 3) Government capital expenditure has a negative effect, both directly and indirectly on unemployment. If government spending increases, unemployment will decrease.